2020
DOI: 10.26501/jibm/2020.1001-013
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Effects of Paternalistic Leadership and Islamic Work Ethics on Employees’ Psychological Safety: Evidence from Pakistan

Abstract: The current study is a contribution in a research area of paternalistic leadership. It examines the relationship between paternalistic leadership and employees' psychological safety with the moderating role of Islamic work ethics. A sample of 359 employees was selected to collect the data from the banking sector of Pakistan by using convenient sampling technique. Time lag design was used to get the data to reduce the common method bias. The results of the study confirmed the positive main effects of paternalis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 76 publications
0
4
0
Order By: Relevance
“…The current study postulates that high level of IWE will create happiness and life satisfaction among the employees and when employees will be satisfied with their life, in turn, their positive behavior toward organization will increase (Park et al, 2021). Previous research has shown that high level of IWE among the employees plays a pivotal role in determining the emotional and psychological states such as workers' psychological capital (Qasim et al, 2021), psychological safety (Khan and Gul, 2020) and psychological distress (Qayyum et al, 2018). This study is different from other, as no prior research to the best of my knowledge has empirically investigated the association between IWE and life satisfaction.…”
Section: Islamic Work Ethics and Life Satisfactionmentioning
confidence: 78%
“…The current study postulates that high level of IWE will create happiness and life satisfaction among the employees and when employees will be satisfied with their life, in turn, their positive behavior toward organization will increase (Park et al, 2021). Previous research has shown that high level of IWE among the employees plays a pivotal role in determining the emotional and psychological states such as workers' psychological capital (Qasim et al, 2021), psychological safety (Khan and Gul, 2020) and psychological distress (Qayyum et al, 2018). This study is different from other, as no prior research to the best of my knowledge has empirically investigated the association between IWE and life satisfaction.…”
Section: Islamic Work Ethics and Life Satisfactionmentioning
confidence: 78%
“…Researchers have shown that substantive attention toward the leadership practices that increase job satisfaction (Shi et al, 2020) critically influences the late working hours and inequalities (Alrawadieh et al, 2020); all of these factors intensify the disturbance of quality of mental health, disturb the work-family balance (Mittal and Bienstock, 2020), and affect the well-being of employees. Thus, the PL attribute reflects that the leader must be expressive; he/she should show the benevolence of a father, dignity, and morally unselfishness (Zorlu, 2019;Khan and Gul, 2020). According to the study by Wang et al (2020), a study on fatherly leadership is flourishing very fast.…”
Section: Literature Review and Hypothesismentioning
confidence: 99%
“…The creativity embedded in the paternalistic leadership leads to organizational readiness to change and this aspect is currently missing in the literature (Du & Luo, 2020;Karakitapoglu-Aygun et al, 2020;Nazir et al, 2020;Soomro et al, 2020). Using LMX as a theoretical lens, the objective of our research is to address the research gap to inspect the association between paternalistic leadership and organizational readiness to change with the mediation of employee engagement and moderation of IWE (Khan & Gul, 2020). This all literature evidence highlights the gap which still exists in the literature and this study will contribute to fulfilling this gap.…”
Section: Introductionmentioning
confidence: 89%